The Effect of Problem-Solving Strategy to Developing Some Physical Abilities and Individual Rapid Attack for Junior Players - Hasan Fadhil Hamzah; Mohammed Rashid Najm (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research problem centered through the researchers’ personal experience. They noticed that there is no use of some trainers for age groups of strategies that are based on the interaction between the teacher and 1 the learner and giving the learner the opportunity, as well as the problems that accompany the education process and the development of physical abilities, which is reflected negatively on their skill performance, especially in the individual rapid attack with a handball and 2 thus not scoring goals and achieving victory in matches, so the researchers decided to go into this experience by using a problem-solving strategy that includes preparing development exercises for the purpose of solving problems that hinder the development of some physical abilities and the individual rapid attack with handball for junior players. The researchers used the experimental approach to design the two equal groups of pre and post-tests to apply the vocabulary of the problem-solving strategy 3, and the research community was determined to apply the problemsolving strategy to the emerging players of the Al-Qasim club, which amounted to (16) players, the sample was divided equally into two experimental and control groups, and after the pre-tests were performed, the members of the experimental group began to apply the units prepared by the researchers and continued for eight weeks every week, three development units. Statistically in the (spss) program.